Passive Double-Sensory Evoked Coherence Correlates with Long-Term Memory Capacity - Horwitz, Anna; Mortensen, Erik L.; Osler, Merete; Fagerlund, Birgitte; Lauritzen, Martin; Benedek, Krisztina (Frontiers in Human Neuroscience, 2017)
Cerebral rhythmic activity and oscillations are important pathways of communication between cortical cell assemblies and may be key factors in memory. We asked whether memory performance is related to gamma coherence in a non-task sensory steady-state stimulation. We investigated forty healthy males born in 1953 who were part of a Danish birth cohort study. Coherence was measured in the gamma range in response to a single-sensory visual stimulation (36 Hz) and a double-sensory combined audiovisual stimulation (auditive: 40 Hz; visual: 36 Hz). The individual difference in coherence (ΔC) between the bimodal and monomodal stimulation was calculated for each subject and used as the main explanatory variable. ΔC in total brain were significantly negatively correlated with long-term verbal recall. This correlation was pronounced for the anterior region. In addition, the correlation between ΔC and long-term memory was robust when controlling for working memory, as well as a wide range of potentially confounding factors, including intelligence, length of education, speed of processing, visual attention and executive function. Moreover, we found that the difference in anterior coherence (ΔCA) is a better predictor of memory than power in multivariate models. The sensitivity of ΔCA for detecting low memory capacity is 92%. Finally, ΔCA was also associated with other types of memory: verbal learning, visual recognition, and spatial memory, and these additional correlations were also robust enough to control for a range of potentially confounding factors. Thus, the ΔC is a predictor of memory performance may be useful in cognitive neuropsychological testing.